EP1179 Keystone flap application in vulvo-perineal reconstructive surgery: a case series of patients with vulvar cancer. (1st November 2019) - Corvetto, E; Proto, A; Fais, M; Locati, V; Russo, M; Figus, A; Candotti, G; Mais, V; Peiretti, M
Abstract : Introduction/Background: This study aimed to evaluate the application of Keystone perforator island flaps (KPIF) technique, complications and long-term results in vulvovaginal reconstruction after wide vulvar surgery. Methodology: This is the first case series describing the technique of Keystone perforator island flaps to close a wide defect after radical vulvectomy. We prospectively collected patient demographics, operative times, intraoperative, early and late complications, pathologic results, and length of stay on all patients. The benefits, cosmetic results and satisfaction of patients were analyze in the follow up. Results: Between December 2016 and July 2018, 5 patients were selected for the study: four patients underwent radical vulvectomy for squamous cell vulvar cancer and one underwent a vulvar wide excision for Paget disease, in all cases a reconstruction with KPIF technique followed the demolitive surgery. The defects were successfully covered by the key stone flap technique in all patients. There were no major intraoperative complications and early postoperative complications such as suture dehiscence occurred in only one patient, suffered a partial dehiscence of the wound. None skin flaps necrosis were observed. All patients were functionally and aesthetically satisfied in the long term. Conclusion: Keystone flaps seems to be easy to design, elevate, and offer rapid fasciocutaneous closure in wide vulvo-perineal defect, with few intraoperative, early and late complications and excellent long-term results. Disclosure: Nothing to disclose